Rakaiz aslamah al-ma'rifah fi tarbiyah al-awlad: qisah Luqman Wa ibnihi Namudhzajan = The pillars of the Islamization of knowledge in raising children: the story of Luqman and his son as a model - Mohammad Asri, Mohammad Afifi; Ahmad H.Osman, Rahmah; Ahmad Borhan, Ahmad Badri; Safin, Muhammad Mamdouh (Al Hikmah Research and Publication Centre, 2022)
Education is one of the most important things in a person's life. The way a person gets upbringing will certainly shape his way of thinking and behaviour. Therefore, education is an important aspect, and special attention must be paid to the formation of the individual with the best man. Education is an element that not only involves the physical aspect, but also emphasizes other aspects such as the spirit and the intellect. The big problem with society in this era is the fall of morals in children. The father and mother failed to raise their children following the Islamic way mentioned in the Qur’an in Surat Luqman. This article aims to analyze this problem by identifying the method of Islamization of knowledge that Luqman used to educate his son, with advice on it.